Pengaruh Nilai-Nilai Islam dalam Pembelajaran Matematika terhadap Peningkatan Kemampuan Berpikir Kritis dan Kreatif Siswa MAN 2 Wonosobo - Dewi Retnowati; Robingun Suyud El Syam; Ahmad Khoiri (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The role of Islamic values in education is crucial, especially in shaping students with strong faith, religious obedience, and noble character. This study aims to analyze the influence of Islamic values integration in mathematics learning on enhancing critical and creative thinking among students at MAN 2 Wonosobo. Using a descriptive quantitative approach, data were collected through questionnaires, observation, and documentation from a sample of 30 students out of a total population of 555. The findings show that applying Islamic values in mathematics learning tends to positively influence students’ critical and creative thinking skills, although the effect is not statistically significant (p > 0.05), largely due to the small sample size. Nevertheless, the results suggest that integrating Islamic values can potentially support students’ cognitive development and character building in the long term. The study recommends innovation, improved measurement tools, and sustained teacher and school commitment for effective integration. Islamic values play a supporting role in creating a meaningful and conducive learning environment, making mathematics not only academically enriching but also character-strengthening.